The protective effect of the intestinal microbiota in type-1 diabetes in NOD mice is limited to a time window in early life - Fernandez Trigo, Nerea; Kalbermatter, Cristina; Yilmaz, Bahtiyar; Ganal-Vonarburg, Stephanie C. (Frontiers in Endocrinology, 2024)
Introduction The incidence of type-1 diabetes is on the rise, particularly in developed nations, and predominantly affects the youth. While genetic predisposition plays a substantial role, environmental factors, including alterations in the gut microbiota, are increasingly recognized as significant contributors to the disease. Methods In this study, we utilized germ-free non-obese diabetic mice to explore the effects of microbiota colonization during early life on type-1 diabetes susceptibility. Results Our findings reveal that microbiota introduction at birth, rather than at weaning, significantly reduces the risk of type-1 diabetes, indicating a crucial window for microbiota-mediated modulation of immune responses. This protective effect was independent of alterations in intestinal barrier function but correlated with testosterone levels in male mice. Additionally, early life colonization modulated T cell subset frequencies, particularly T helper cells and regulatory T cells, in the intestine, potentially shaping type-1 diabetes predisposition. Discussion Our findings underscore the pivotal role of early-life microbial interactions in immune regulation and the development of autoimmune diseases.